APPEAL‐2: A pan‐European qualitative study to explore the burden of peanut‐allergic children, teenagers and their caregivers. Issue 11 (15th September 2020) - DunnGalvin, Audrey; Gallop, Katy; Acaster, Sarah; Timmermans, Frans; Regent, Lynne; Schnadt, Sabine; Podestà, Marcia; Sánchez, Angel; Ryan, Robert; Couratier, Pascale; Feeney, Mary; Hjorth, Betina; et al.
Abstract: Background: Allergy to Peanuts ImPacting Emotions And Life (APPEAL‐1) was a recent European multi‐country questionnaire survey that highlighted the negative impacts of peanut allergy (PA) on quality of life. A follow‐on qualitative study, APPEAL‐2, further assessed the burden of PA and associated coping strategies through semi‐structured interviews. Objective: To gain qualitative insight on the strategies used to cope with and manage PA and the impact of these strategies on the quality of life of children, teenagers and caregivers. Methods: This cross‐sectional qualitative study was conducted in eight European countries: the United Kingdom, France, Germany, Ireland, Spain, Italy, Denmark and the Netherlands. Semi‐structured interviews were conducted with children (aged 8‐12 years) and teenagers (aged 13‐17 years) with self‐/proxy‐reported moderate or severe PA and with parents/caregivers of children or teenagers (aged 4‐17 years) with moderate or severe PA. Data were analysed using thematic analysis; data saturation was assessed. Two conceptual models were developed to illustrate the impacts of PA and coping strategies used to manage them for (a) individuals with PA and (b) parents/caregivers of children with PA. Results: 107 participants were interviewed: 24 children, 39 teenagers and 44 caregivers. The conceptual models illustrated themes related to coping and control, driven by the fear of PA reactions, and the associated emotional, social, relationship and work impacts. Factors moderating these impacts included social attitudes and support, child‐caregiver relationship and coping strategies used. Conclusions and Clinical Relevance: The APPEAL‐2 results substantiate the findings of APPEAL‐1; the results also suggest that the severity of experience with PA may not correlate with perception of its overall burden and show variable impacts by country.